An intraspecific structure of Сicindela (s. str.) coerulea Pallas, 1773 (Coleoptera, Cicindelidae) - Matalin, Andrey V. (Zootaxa, 2025)
An intraspecific structure of a widely distributed Asian species of tiger beetle, Сicindela coerulea Pallas, 1773, is revised and discussed. The neotype of Cicindela coerulea Pallas, 1773 as well as the lectotypes and paralectotypes of Cicindela optata Fischer von Waldheim, 1828, Cicindela przewalskii Dokhtouroff, 1887, Cicindela przewalskii var. grumi Tschitschérine, 1902 and Cicindela przewalskii var. kozlovi Tschitschérine, 1902 are designated. The new synonymy is established: Cicindela coerulea coerulea Pallas, 1773 = Cicindela coerulea lucifera Mandl, 1970, syn. nov. Cicindela coerulea selengensis Mandl, 1936 is considered a synonym of Cicindela coerulea nitida Lichtenstein, 1796, and Cicindela coerulea kozlovi Tschitschérine, 1903 is considered a synonym of Cicindela coerulea grumi Tschitschérine, 1903. The distribution map and an identification key are provided. The geographic variability of the basic colour and the white elytral pattern is discussed as well.